The Application of Pastel Color Palettes and Visual Psychology to Enhance Visual Focus in Children's Picture Books - Avierry Fionarizoca; Dianing Ratri (PANTUN: Jurnal Ilmiah Seni Budaya, 2026)
Children’s picture books provide young readers with stories and visual environments that shape their early reading experiences. In recent years, the use of pastel colour palettes has become more visible in the illustration of Indonesian children’s books, particularly those that are targeted at early childhood audiences. This study investigates the use of pastel colour in selected picture books published by Pelangi Indonesia and discusses its visual characteristics based on colour theory and visual psychology. The analysis is based on a qualitative descriptive approach in the field of visual communication design (VCD) and discusses the colour relationships, contrast, composition and layout organization. The results show that pastel colours are always accompanied by balanced compositions and moderate visual contrasts, in order to create illustrations that emphasise visual softness and harmony. From the visual psychology perspective, these features might be helpful to build a more comfortable and calm reading environment for the children aged 4-6 years. The study shows that pastel-based illustration design is a beneficial approach to developing visually supportive learning materials. It is a contribution to the ongoing discussion of the use of colour in early childhood visual communication.